Formal and Informal Learning and First-Year Psychology Students’ Development of Scientific Thinking: A Two-Wave Panel Study - Soyyılmaz, Demet; Griffin, Laura M.; Martín, Miguel H.; Kucharský, Šimon; Peycheva, Ekaterina D.; Vaupotič, Nina; Edelsbrunner, Peter A. (Frontiers in Psychology, 2017)
Scientific thinking is a predicate for scientific inquiry, and thus important to develop early in psychology students as potential future researchers. The present research is aimed at fathoming the contributions of formal and informal learning experiences to psychology students’ development of scientific thinking during their first year of study. We hypothesize that informal experiences are relevant beyond formal experiences. First-year psychology student cohorts from various European countries will be assessed at the beginning and again at the end of the second semester. Assessments of scientific thinking will include scientific reasoning skills, the understanding of basic statistics concepts, and epistemic cognition. Formal learning experiences will include engagement in academic activities which are guided by university authorities. Informal learning experiences will include non-compulsory, self-guided learning experiences. Formal and informal experiences will be assessed with a newly developed survey. As dispositional predictors, students’ need for cognition and self-efficacy in psychological science will be assessed. In a structural equation model, students’ learning experiences and personal dispositions will be examined as predictors of their development of scientific thinking. Commonalities and differences in predictive weights across universities will be tested. The project is aimed at contributing information for designing university environments to optimize the development of students’ scientific thinking.